Designing socio discovery learning with interactive multimedia for entrepreneurship education: A mixed method approach - Wardani, Dewi Ayu Wisnu; Sunardi; Asrowi; Widyastono, Herry (Edelweiss Applied Science and Technology, 2024)
This research is motivated by the necessity for a more effective learning model aimed at enhancing students’ communication skills in vocational schools, particularly in the subject of Creative Products and Entrepreneurship (CPE). Currently, the implementation of ICT-based learning remains limited, resulting in an underutilization of technological potential. The objective of this study is to develop a Socio Discovery Learning model that incorporates interactive multimedia to support the improvement of students’ communication skills. The research employs a mixed methods design, involving 64 vocational students and two teachers as research subjects. Data were collected through questionnaires, interviews, and classroom observations. Findings from the interviews and observations indicate that teachers face challenges in applying Socio Discovery Learning, primarily due to limited technological facilities and a lack of training in the use of interactive media. Student survey results reveal that 75% of students believe that more interactive ICT-based media would enhance their learning experience, and 80% express a desire for such media to be utilized more frequently in their education. Although Discovery Learning has been implemented, its usage remains suboptimal. Overall, the development of an interactive multimedia-based Socio Discovery Learning model holds significant potential for improving students’ communication skills.